Characterising population spatial structure change in Chinese cities. (April 2022) - Xi, Yu; Qiang, Li; Zhengdong, Huang; Renzhong, Guo
Abstract: Urbanisation has drastically altered the population structure of cities worldwide. Quantitative measurement and analysis of changes in population density may provide insights into urban system modelling and urban planning. Population distribution modelling has been performed previously; however, to the best of our knowledge, the spatial dynamics of population density change have not yet been fully explored. In this study, we constructed a linear combination (LC)-lognormal model and proposed six characteristic indices to fill this gap. Based on the model, we presented four patterns of population spatial structure change (PSSC): Growing, Shrinking, Decentralising, and Centralising. The model was then applied to 213 monocentric cities on the Chinese mainland during 2000–2010. PSSCs of over 88.7% of cities could be properly characterised using the LC-lognormal model. The main findings include the following: (1) the most dramatic population change typically occurred close to the city centre, and (2) shrinking pattern may be influenced by drastic urban land expansion with inadequate economic growth. This study may supplement the methodology of population spatial structure studies and contribute to the knowledge on PSSCs in different cultures and policy frameworks. Highlights: A LC-lognormal model built to fit the gradient of population density change. Indices proposed to characterise patterns of population spatial structure change. Most Chinese cities can be properly characterised using the LC-lognormal model. The most dramatic population change generally occurs close to the city centre. Most Pattern B (shrinking) cities experienced drastic urban land expansion.